Adenocarcinoma of the caecum metastatic to the bladder: an unusual cause of haematuria - Grey, Benjamin R (BioMed Central, 2006)
BACKGROUND: Primary malignancies of colorectal origin can metastasise to the bladder. Reports are however extremely rare, particularly from the caecum. CASE REPORT: The report describes the case of a 45-year old male with Duke's B caecal carcinoma treated with a laparoscopically-assisted right hemicolectomy and adjuvant 5-Fluorouracil chemotherapy. Subsequently, a metastatic lesion to the bladder was demonstrated and successfully excised by partial cystectomy. CONCLUSION: In order that optimal therapeutic options can be determined, it is important for clinicians to distinguish between primary disease of the bladder and other causes of haematuria. Various immunohistochemical techniques attempt to differentiate primary adenocarcinoma of the bladder from secondary colorectal adenocarcinoma. Suspicion of metastatic disease must be raised when histologically unusual bladder tumours are identified.